Significant challenges of COPD Management in developing countries - Saadia Ashraf; Andrew Owuor; Sumedha Heenagamage; Naghman Bashir; Syed Munis Ul Hasan; Jahanzeb Kamal Khan; Salim Rashid Masoud; Dhamith Nandadeva; Maqbool Ahmed (Journal of the Pakistan Medical Association, 2023)
To explore the challenges faced by each stakeholder for COPD management, including the patients, their family/caretakers, healthcare professionals, and healthcare policymakers & organizations, the authors conducted a survey during the International Respiratory Forum conference 2022 in Ho Chi Minh City, Vietnam. A total of 140 pulmonologists from 11 countries participated in the study. A predesigned structured questionnaire was developed pertaining to questions related to challenges faced by each stakeholder for COPD management in Low-middle income countries (LMIC). Each group received one of the four sections of the questionnaire. It was found that 47% of doctors thought that patients couldn’t understand the early symptoms as indicators of a serious illness and were afraid of forming a dependency on long-term drugs. According to 64% of doctors, the most frequent implications experienced by caregivers when caring for COPD patients were the financial burden of lifelong therapies and disappointments from treatment failure brought on by a lack of access to high-quality or specialized healthcare. Of the difficulties experienced by healthcare professionals, 50% said that misusing investigations for diagnosis resulted in delayed or underdiagnoses of COPD. The biggest issue with COPD referrals in developing nations was general practitioners’ ignorance of recognizing highrisk patients and the need for their referrals. Approximately 80% of respondents said that a sizeable percentage of annual healthcare spending was consumed by expenses related to exacerbations and repeated ER visits. It is concluded that the questionnaire responses reflect physicians’ perceptions and experiences in routine clinical practice. Increased knowledge of COPD diagnosis and treatment recommendations, as well as proactive identification of patients at higher risk of developing COPD due to environmental or lifestyle exposures, will help with prompt, accurate diagnoses and efficient treatments, ultimately improving patient outcomes. Keywords: COPD Management, Challenges, Developing Countries.